Genetic characterization, antibiogram pattern, and pathogenicity of Clostridium perfringens isolated from broiler chickens with necrotic enteritis - Eraky, R. D.; Abd El-Ghany, W. A. (Journal of the Indonesian Tropical Animal Agriculture, 2022)
The aims of this investigation were characterization, demonstration of the antibiogram pattern and detection of the pathogenicity of Clostridium perfringens (C. perfringens) strains isolated from broiler chickens in Damietta governorate, Egypt. A total of 357 samples representing 202 intestinal contents and 155 liver samples from freshly dead broiler chickens were collected from 18 broiler farms. Isolates of C. perfringens were identified morphologically, microscopically, and biochemically. Forty-seven C. perfringens isolates were recovered, which represented 20.3% of the intestinal contents and 3.8% of the liver samples. The toxins and virulence genes of C. perfringens were investigated using polymerase chain reaction. All of the toxigenic C. perfringens strains were type A and carried netB, tpeL, cpe, and plc genes. The in vitro antibiogram of C. perfringens strains revealed 100% sensitivity to gentamycin and levofloxacin and 100% resistance to nalidixic acid and ceftriaxone. The isolated C. perfringens strains were highly pathogenic and induced signs and lesions of necrotic enteritis as well as 43.3% mortalities in 20-day-old chicks. In conclusion, C. perfringens is an important pathogen that affects broiler chickens due to the presence of virulence genes and the pathogenicity in the inoculated birds.